FC062: Baseline Soluble Immune Checkpoints Predict Relapse Risk in PR3-Anca Vasculitis Following Rituximab Induction Therapy. (3rd May 2022) - Kronbichler, Andreas; Gamerith, Gabriele; Mildner, Finn
Abstract: BACKGROUND AND AIMS: We investigated whether soluble immune checkpoints (sICPs) predict treatment-resistance, relapse risk and risk of infections in patients with antineutrophil cytoplasm antibody (ANCA)-associated vasculitis (AAV). METHOD: Plasma levels of sICPs were measured by enzyme-linked immunosorbent assay from samples obtained at baseline and during follow-up from patients with AAV in the RAVE trial and were correlated with selected clinical outcomes. Log-rank test was used to evaluate survival benefits, and optimal cut-off values of the marker molecules were calculated using Yeldons J. RESULTS: Among 95 patients receiving rituximab as induction therapy, lower soluble (s)Lag-3 (<90 pg/mL) and higher sCD27 (>3000 pg/mL) were predictive of not achieving remission. Among patients with remission, 32.9% relapsed with a median relapse free survival of 5.64 months. Low baseline values of sTim-3 (<1200 pg/mL), sCD27 (<1250 pg/mL) and sBTLA (<1000 pg/mL) were associated with disease relapse. In addition, patients with high levels of at least one of these markers were prone to infectious complications. These findings were restricted to patients with proteinase 3 (PR3)-ANCA vasculitis and not observed in patients with myeloperoxidase (MPO)-ANCA vasculitis. Moreover, these relationships do not hold for the group of patients randomized to receive cyclophosphamide/azathioprine. CONCLUSION: Rituximab-treated patients achieved remission less frequently when sLag-3 was low and sCD27 was high. Higher expression of sTim-3, sCD27 and sBTLA at baseline was associated with a lower risk of relapse in PR3-ANCA vasculitis following rituximab. These results will require confirmation in future studies, but may contribute to personalized medicine in AAV.